2013
DOI: 10.3803/enm.2013.28.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Thyroid Stimulating Hormone Receptor mRNA in Mouse C2C12 Skeletal Muscle Cells

Abstract: BackgroundWe analyzed whether thyroid stimulating hormone receptor (TSH-R) is expressed in a skeletal muscle cell line and if TSH has influence on the differentiation of muscle cells or on the determination of muscle fiber types.MethodsTSH-R gene expression was detected with nested real-time polymerase chain reaction (RT-PCR) in C2C12, a mouse skeletal muscle cell line. The effect of TSH on myotube differentiation was assessed by microscopic examination of myotube formation and through the measurement of expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…TSH receptors have been found in numerous tissues, including the liver (39), adipose tissue (40) and bone (41). However, there is scarcity of data regarding TSH receptors in human skeletal muscle cells, with receptors found mostly in extraocular muscles (42) and cardiomyocytes (43), as well as C2C12 mouse skeletal muscle cells (44). In addition, although muscle-containing organs are the primary sites of irisin secretion (14), it was shown that irisin is expressed in other organs and mainly in adipose tissue, especially in states of increasing obesity (10, 45).…”
Section: Discussionmentioning
confidence: 99%
“…TSH receptors have been found in numerous tissues, including the liver (39), adipose tissue (40) and bone (41). However, there is scarcity of data regarding TSH receptors in human skeletal muscle cells, with receptors found mostly in extraocular muscles (42) and cardiomyocytes (43), as well as C2C12 mouse skeletal muscle cells (44). In addition, although muscle-containing organs are the primary sites of irisin secretion (14), it was shown that irisin is expressed in other organs and mainly in adipose tissue, especially in states of increasing obesity (10, 45).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have shown that a low-TSH concentration is associated with low grip strength in older patients with DTC. Although we believe that TSH may regulate the biogenesis and molecular function of skeletal muscle cells ( 14 ), further experimental studies are required to define the effects of TSH on muscle physiology and pathology in the context of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it remains to be elucidated how excessive T4 supplementation-induced subclinical hyperthyroidism affects muscle mass and function after total thyroidectomy in differentiated thyroid cancer patients. In addition, recent studies have shown that the TSH receptor is expressed in skeletal muscle cells ( 14 , 15 ). TSH also directly modulates muscle metabolism, independently of thyroid hormone, as has been demonstrated with respect to bone remodeling ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the roles of thyroid hormones in skeletal muscle, TSH is also suggested to have a role in muscular metabolism. ough the exact role of TSH in skeletal muscle physiology has not been fully evaluated, the presence of TSH receptors and a functional role of TSH in energy metabolism in skeletal muscle have been presented [32,33]. erefore, correlation of muscle strength and thyroid function, which would be represented by thyroid hormone and TSH, could be suspected.…”
Section: Discussionmentioning
confidence: 99%